Prognostic factors and mitotane treatment of adrenocortical cancer. Two decades of experience from an institutional case series - Tőke, Judit; Uhlyarik, Andrea; Lohinszky, Júlia; Stark, Júlia; Huszty, Gergely; Micsik, Tamás; Borka, Katalin; Reismann, Péter; Horányi, János; Igaz, Peter; Tóth, Miklós (Frontiers in Endocrinology, 2022)
Objectives This study aimed to characterise the clinicopathological features and prognostic factors of a large cohort of Hungarian patients with adrenocortical cancer diagnosed between 2000-2021. Patients and methods This retrospective study included seventy-four patients (27 men and 47 women) with histologically confirmed adrenocortical cancer in a single tertiary referral endocrine centre. Descriptive statistics were performed, providing summaries of selected clinical and pathological parameters. Clinicopathological factors contributing to overall survival were analysed. Results The median age of patients was 48,5 years (17-84 years) at diagnosis. The majority of cases were diagnosed at ENSAT stage II (39,2%) and stage IV (33,8%). At diagnosis, the median tumour size was 9,0 cm (4,5-20 cm). In 47 patients (71,6%), the tumour was hormonally active. The median overall survival and the 5-year survival rate were 23,5 months (95% CI, 17-30,5 months) and 18,3%, respectively. Primary tumour resection was performed in 68 patients (91,8%); R0 surgical resection was achieved in 30 patients. In univariate Cox regression model, tumours with stages III and IV, high proliferative activity (Ki67-index > 10%), R1-R2 surgical resection state and hormonal activity were associated with poorer survival. Cortisol excess, both isolated and combined with androgen production, was associated with poorer survival. Fifty-five patients were treated with mitotane. The overall survival of patients achieving therapeutic mitotane plasma concentration was significantly better compared to those who never reached it [27.0 (2-175) months vs 18.0 (2-83) months; p<0.05)]. The median age, the distribution of gender, ENSAT stage, resection state and Ki67-index did not differ between these two groups. The time needed to reach the therapeutic range of serum mitotane was 96.5 days (95% CI, 75-133 days). Conclusion Our results confirm previous data that disease stage, mitotic activity, the resection state and the mitotane treatment achieving therapeutic concentration are the most critical parameters influencing the prognosis of adrenocortical cancer. Our data suggest that hormonal activity may be more frequent than described previously, and it is a strong and independent prognostic factor of overall survival. To our knowledge, this is the first single-centre study confirming the prognostic importance of achieving therapeutic mitotane concentration.